Some Reflections on the Limitations to Public Participation in the Post-Political City - Ronan Paddison (L'Espace Politique)
Neoliberal practices are the new orthodoxy within urban governance imposing limits to participatory and more democratic forms of engagement in the city, particularly where they challenge the official discourses through which cities strive to be competitive spaces in the globalizing economy. This paper offers a theoretical understanding of these limits through two related propositions. First, that urban governance has assumed a post-political configuration; second, and reflecting such a configuration, urban entrepreneurialism is becoming defined by a new style of politics, urban neo-populism. Against the disciplining imperative of creating the competitive city, neo-populism becomes defined around the manufacture of consensus politics, the effect of which is to marginalize protest and dissensus.